A Diaporthe Fungal Endophyte From a Wild Grass Improves Growth and Salinity Tolerance of Tritordeum and Perennial Ryegrass - Toghueo, Rufin M. K.; Zabalgogeazcoa, Iñigo; Pereira, Eric C.; Vazquez de Aldana, Beatriz R. (Frontiers in Plant Science, 2022)
Some microbiome components can provide functions that extend the capabilities of plants, increasing the environmental adaptability and performance of holobionts. Festuca rubra subsp. pruinosa is a perennial grass adapted to rocky sea cliffs, where soil and nutrients are very limited, and exposure to salinity is continuous. This study aimed to investigate if a Diaporthe fungal endophyte belonging to the core microbiome of Festuca rubra roots could improve the performance of two agricultural grasses. In a greenhouse experiment, plants of tritordeum (Triticum durum x Hordeum chilense) and perennial ryegrass (Lolium perenne) were inoculated with Diaporthe strain EB4 and subjected to two salinity conditions (0 mM and 200 mM NaCl). Biomass production, mineral elements, proline, hormone profiles, antioxidant capacity and total phenolic compounds were examined in plants and fungal functions potentially related to the promotion of plant growth were determined. The inoculation with Diaporthe promoted plant growth of both grasses, increasing leaf biomass (84% in tritordeum and 29% in perennial ryegrass), root biomass, nutrient content (N, Ca, Mg and Fe), and the production of indole 3-acetic acid, regardless of the salinity treatment. Improved growth and nutrient uptake might occur because Diaporthe produces several extracellular enzymes capable of recycling organic nutrient pools. In addition, the fungus produced indole 3-acetic acid in vitro and modulated the production of this phytohormone in the plant. Under salinity, the activity of Diaporthe ameliorated the stress, increasing proline, nutrient uptake in roots, gibberellins and indole 3-acetic acid, which in turns results into improved growth. Thus, this fungus can transfer to alternative hosts some advantages useful at its original habitat.